2016
DOI: 10.1186/s11671-016-1712-2
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide-Gallic Acid Nanodelivery System for Cancer Therapy

Abstract: Despite the technological advancement in the biomedical science, cancer remains a life-threatening disease. In this study, we designed an anticancer nanodelivery system using graphene oxide (GO) as nanocarrier for an active anticancer agent gallic acid (GA). The successful formation nanocomposite (GOGA) was characterized using XRD, FTIR, HRTEM, Raman, and UV/Vis spectroscopy. The release study shows that the release of GA from the designed anticancer nanocomposite (GOGA) occurs in a sustained manner in phospha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
44
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 81 publications
(51 citation statements)
references
References 55 publications
5
44
1
1
Order By: Relevance
“…The nanodrug delivery platform is a subject of rapid growth because of its significant role in the improvement of therapeutic values of different drugs and bioactive molecules by modulating their release profiles, bioavailability, and solubility, and protecting the drug from degradation [ 5 , 12 , 13 ]. Increased efforts are now being invested into engineering multifunctional, biocompatible nanomaterials for the delivery of drugs at the site of infection thereby resulting in more effective therapy [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…The nanodrug delivery platform is a subject of rapid growth because of its significant role in the improvement of therapeutic values of different drugs and bioactive molecules by modulating their release profiles, bioavailability, and solubility, and protecting the drug from degradation [ 5 , 12 , 13 ]. Increased efforts are now being invested into engineering multifunctional, biocompatible nanomaterials for the delivery of drugs at the site of infection thereby resulting in more effective therapy [ 14 , 15 , 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the burst effect that presence in the graph of the Na3PO3 solution may occur due to the surface characteristics of a graphite oxide material, the herbicide interactions and porous structure of the material [9]. The characteristics of the mechanism of the ion-exchange method would not lead the percentage of MCPA anion released from MCPA-GO nanocomposite at equilibrium reach 100%.…”
Section: Controlled Release Studiesmentioning
confidence: 99%
“…It is because they are facilitating the good targeting, high loading and control release of drugs/herbicides. By exploring the area drugs delivery system, Barahuie et al [8] have reported the graphite oxide as a nanocarrier for the active anticancer agent of chlorogenic acid while Dorniani et al [9], makes their research on gallic acid as a cancer therapy by using the graphite oxide too. Besides that, Yu et al [10] did some modification in their work to make the graphite oxide being able to be as a nanocarrier loaded with anticancer herbal drug berberine by combined the graphite oxide with PEG.…”
Section: ■ Introductionmentioning
confidence: 99%
“…These groups suggest the presence of AuNPs. 28,29 TeM and eDX analysis of auNPs synthesized from sx TEM imaging uses a narrow beam of electrons focused on the sample and measures the size of the particle accurately. TEM images showed AuNPs as dark spots against a light background.…”
Section: Ftir Analysis Of Aunps Synthesized From Sxmentioning
confidence: 99%